CLINICAL SIGNIFICANCE OF HEART RATE VARIABILITY INDEXES DERIVED FROM 5-MINUTE AND 24-HOUR ECG RECORDINGS IN PATIENTS WITH RHEUMATOID ARTHRITIS - D. A. Anichkov; A. A. Platonova (Рациональная фармакотерапия в кардиологии)
Aim. To estimate heart rate variability (HRV) from 5-min and 24-h electrocardiogram (ECG) recordings in female patients with rheumatoid arthritis (RA) and patients of control group, to analyze association between HRV indexes and cardiovascular risk factors and RA-related clinical characteristics.Material and Methods. 90 female patients with RA and 30 healthy subjects matching for age were included in the study. The baseline evaluation included a physical examination, assessment of the cardiovascular risk factors and RA clinical characteristics, laboratory tests, 5-min and 24-hour ECG recordings. We analyzed the time-domain (SDNN, rMSSD, pNN50), frequency-domain (LF, HF, LF/HF ratio) and nonlinear indexes (SD1, SD2, SD21) of HRV from 5-min ECG recording and the time-domain (SDNN, rMSSD, pNN50) indexes from 24-h ECG recordings.Results. Patients with RA had lower HRV in comparison with control subjects (p<0,05). We got the following results for 5-min ECG recordings: time-domain (SDNN, rMSSD, pNN50), frequency-domain (LF, HF) and nonlinear indexes (SD1, SD2) negatively correlated with erythrocyte sedimentation rate (ESR) (р<0,05). All parameters of HRV (except for pNN50) strongly negatively correlated with disease activity score (DAS28). LF and HF levels depended on age. The analysis of 24-h ECG recordings showed negative correlation of timedomain indexes (SDNN, rMSSD, pNN50) with DAS28 and ESR.Conclusion. Reduced HRV is associated with inflammation activity in patient with RA. Low level of HRV and high RA activity are unfavorable cardiovascular factors.